Implementing a Global Health Qualitative Research Study: Experiences of a Project Coordinator in Uganda - Kastner, Jasmine; Milford, Cecilia; Akatukwasa, Cecilia; Kembabazi, Annet; Smit, Jenni (The East African Health Research Journal, 2017)
Qualitative research in global health requires substantial operational and logistical support during both the implementation phase and day-to-day operations. However, little to no published work shares the experiences of international qualitative research teams. Yet, without a strong project foundation and attention to everyday details, studies can begin without appropriate guidance and, as a result, poor quality data may be generated. This paper presents a detailed account of a project coordinator’s experience implementing 4 qualitative HIV and reproductive health studies in Uganda between 2012 and 2014, reflecting on our research team’s practices and lessons learnt, and provides recommendations for successful project implementation. The aim of this paper is to help new global health qualitative project coordinators, and international teams more generally, by detailing 6 coordination tasks: hiring, training, team communication, organization of study documents, data collection and storage, and research ethics. To avoid repeat learning of basic, yet important, logistical steps by each new qualitative research project coordinator, this paper can help coordinators think about how to organize their work in order to prepare for both planned and unplanned challenges that have been encountered by others. Sharing operational and logistical experiences and expertise can benefit the global health community and help future studies run more efficiently.
Keywords: GlobalHealth; Qualitative research; Uganda